2018
DOI: 10.1101/442822
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

I knew that! Response-based Outcome Predictions and Confidence Regulate Feedback Processing and Learning

Abstract: Influential theories emphasize the importance of predictions in learning: We learn from response outcomes and feedback to the extent that they are surprising, and thus convey new information.Here we investigated how individuals learn to predict response outcomes based on the subjective confidence and objective accuracy with which these predictions are made. We hypothesized that both of these aspects modulate how feedback is processed and that they are reflected in eventrelated potentials (ERPs) as measured usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 100 publications
(132 reference statements)
3
10
1
Order By: Relevance
“…We found a different pattern of results when examining the feedback-related negativity (FRN), which typically indexes the difference in feedback-locked activity for trials that resulted in negative compared to positive feedback 46 . Consistent with previous findings [47][48][49][50][51][52] , we found a reliable effect of receipt vs omission of reward on FRN amplitude (b = 0.80, p <.001), and this effect was enhanced for high reward trials (b = 0.81, p = .007; Table S9). However, in addition to this, and contrary to the hypothesis we preregistered based on previous findings 53, 54 , we found that effects of reward receipt vs omission on FRN amplitude were reduced for trials with high efficacy compared to those with low efficacy (b = -0.83, p = .007; Fig.…”
Section: Influences Of Incentives On Eeg Signatures Of Response and Fsupporting
confidence: 91%
See 1 more Smart Citation
“…We found a different pattern of results when examining the feedback-related negativity (FRN), which typically indexes the difference in feedback-locked activity for trials that resulted in negative compared to positive feedback 46 . Consistent with previous findings [47][48][49][50][51][52] , we found a reliable effect of receipt vs omission of reward on FRN amplitude (b = 0.80, p <.001), and this effect was enhanced for high reward trials (b = 0.81, p = .007; Table S9). However, in addition to this, and contrary to the hypothesis we preregistered based on previous findings 53, 54 , we found that effects of reward receipt vs omission on FRN amplitude were reduced for trials with high efficacy compared to those with low efficacy (b = -0.83, p = .007; Fig.…”
Section: Influences Of Incentives On Eeg Signatures Of Response and Fsupporting
confidence: 91%
“…Epochs containing artifacts, with amplitudes exceeding ±150 µV or gradients larger than 50 µV, were excluded from further analysis. We focused our analyses on these event-related potentials, quantified agnostic of condition with ROIs and time-windows determined a priori based on the literature : cue-locked P3b (250 to 550 ms, averaged across Pz, P3 and P4 27,83 ), cue-locked late contingent negative variations (CNV; to 1500 ms post-cue, i.e., -500 to 0 ms pre-target, averaged across Fz, FCz, and Cz 30 ), response-locked correct-and error-related negativities (CRN/ERN; 0 to 100 ms 43,84 ), and feedback-locked feedback-related negativity (FRN; quantified peak-to-peak at FCz as the difference between the negative peak between 250 to 350 ms and the positive peak in the preceding 100 ms from the detected peak 85 ). All EEG data preprocessing were performed using custom MATLAB scripts using EEGLAB functions (cf.…”
Section: Studymentioning
confidence: 99%
“…The priors were very wide Gaussian distributions for both the intercept (M = 5; SD = 5) and the slopes (M = 0; SD = 5; cf. Fischer & Ullsperger, 2013;Frömer, Nassar, et al, 2018).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…All three models included intercept as a constant and a varying effect, and constant main effects in the varying effect structure. We selected wide Gaussian priors based on previous studies (Fischer & Ullsperger, 2013;Frömer, Nassar, et al, 2018) for both the intercept (M = 0; SD = 5) and the slopes (M = 5; SD = 5).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Subjective confidence is used to weight prior knowledge and incoming evidence by their respective reliability [110]. Individuals with a better correspondence between confidence judgments and prediction accuracy learn more quickly [119]. Individuals with better metacognitive accuracy for a perceptual decision are also better able to learn novel arbitrary cue-stimulus associations for the stimuli the perceptual decision was based on [120].…”
Section: Learningmentioning
confidence: 99%